Immobilization of Jacobsen type catalysts on modified silica (2011)
RESUMEN: Several immobilized Jacobsen type catalysts were covalently anchored on modified SiO2 using 3-aminopropyltriethoxysilane (3-APTES) as a reactive surface modifier. Characterization of the heterogeneous catalysts, as well as their precursors, by FTIR, DR UV–VIS, TGA and AAS confirms the successful immobilization of chiral Mn(III) salen complexes. These catalysts were examined for the diastereoselective epoxidation of R-(+)-limonene with in situ generated dimethyldioxirane (DMD) as oxidizing agent, yielding 1,2-epoxide as the main product. When compared to homogeneous catalysts, under similar experimental conditions, only a slight selectivity decrease over heterogeneous catalysts was observed. The immobilized catalysts were used three times maintaining the initial selectivity. However, after reusing them more than three times, selectivity to 1,2-epoxide decreased. FTIR results suggest partial degradation of the catalytic species. Despite the immobilization method was chosen to minimize changes in the structure of the homogeneous catalysts the diastereoselectivity (d.e.) of heterogeneous catalysts underwent a remarkable decay.